Critical Dogmatics as Paradigm. Issue 3 (4th September 2017) - Hinlicky, Paul R.
Abstract: Theology as "critical dogmatics" points to a way forward between naturalism and constructivism in thought "after modernity." It urges neither pre‐critical dogmatics nor modern systematizing, but a proposal for a pragmatic and hermeneutical theology making a single claim to truth about God as the One determined to redeem and fulfill the creation through the missions of God's Son and Spirit. This article clarifies the difference between Rudolph Bultmann's program of demythologization, and more generally, dialectical theology's antinomy of "the word of God and the word of humans, " and the sense of "deliteralization" in the strong trinitarian personalism of critical dogmatics.